2021
DOI: 10.1177/01632787211040859
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Health Care Evaluation Instruments: A Review of Psychometric Evidence

Abstract: Teamwork among health care professionals has been found to improve patient outcomes and reduce burnout. Surveys from individual team members are often used to measure the effectiveness of teamwork performance, as they provide an efficient way to capture various constructs of teamwork. This allows evaluators to better understand team functioning, areas of strength, and to identify potential areas for improvement. However, the majority of published surveys are yet to be validated. We conducted a review of psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Based on Kang et al . research, CPAT provided a compatible tool to measure teamwork in a general medical care setting [ 26 ]. The domains were derived from current literature about the interprofessional collaborative framework and it was one of few scales that emphasized “patient involvement” as one of the collaborative tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Kang et al . research, CPAT provided a compatible tool to measure teamwork in a general medical care setting [ 26 ]. The domains were derived from current literature about the interprofessional collaborative framework and it was one of few scales that emphasized “patient involvement” as one of the collaborative tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The results of item-level analysis showed that the failure indicators of all items were <3, thus there were no failure items in T-CAPT [ 24 - 26 ]. According to Tu JT.…”
Section: Discussionmentioning
confidence: 99%
“…The review conducted by Kang et al (Kang et al, 2022) presented seven instruments designed for the assessment of collaborative efforts within health care teams. Most of these instruments consist of objective and quantitative items related to attributes that lead to the socio-affective interactions established between health care professionals, including communication, role definition, and decision-making.…”
Section: Learning Assessment Instruments In the Health Contextmentioning
confidence: 99%
“…These strategies encompass elements such as teamwork, role definition, communication, feedback, learning, reflective thinking, patient-centred focus, and ethical conduct. Some authors deem it essential to undertake research focused on the development and evaluation of learning assessment instruments tailored for use within collaborative settings comprising varied health care professionals (Kang et al, 2022;Thistlethwaite et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…CPAT is acceptable for use in many different clinical settings, such as primary and community care [ 29 , 33 ], mental health [ 23 ], chronic disease management [ 28 ], health professionals postgraduate training [ 24 ], patient safety [ 30 ], and patient satisfaction [ 32 ]. Despite its lengthy scale consisting of 56 items, the CPAT is recommended as the best instrument for measuring interprofessional collaboration for teamwork [ 34 ]. All of these studies included health professionals as participants.…”
Section: Introductionmentioning
confidence: 99%